Mid-life predictors of late-life depressive symptoms; determining risk factors spanning two decades in the Women's Heathy Ageing Project - Katherine E. Campbell; Alexandra Gorelik; Cassandra E. Szoeke; Lorraine Dennerstein (BMC, 2020)
Abstract Background Data available from longitudinal studies of adequate duration to explore midlife risk factors for late life higher depressive symptom scores in women is lacking. This study examines midlife (mean ages 50 years and 60 years) predictors of late life (mean age 70 years) depressive symptom scores to enrich our understanding of the role of changing risk factors across the lifespan. Methods This investigation was an assessment of the long-term impact of lifestyle and health variables on depressive symptoms. Data were drawn from an epidemiological prospective study of women's healthy ageing spanning two decades. Variables included assessment of mood, demographics, physical health, smoking status, attitudes towards ageing and menopause, alcohol consumption and employment. Analysis was conducted to determine the set of strongest predictors assessed in 1992 (mean age 50 years) and in 2002 (mean age 60 years) in relation to higher CESD-SF scores measured in 2012 (mean aged 70 years (n = 249)). A cross-sectional analysis determining concurrent associations at mean age 70 years was also conducted. Results An increase in positive mood at 50 and 60 years was associated with a 0.3 (95% CI 0.1-0.5) and 0.4 (95%CI 0.1-0.8) point reduction in CESD score at 70 years respectively. An increase in Hassles score at age 50 was associated with a 0.18-point increase in CESD (95% CI 0.01-0.05) 20 years later. However, no relationship was observed between Hassles score at 60 and CESD 10 years later. Analysis of concurrent risk factors demonstrated that bothersome symptom frequency and higher anxiety were associated with higher depressive symptom scores when women were 70 years. Conclusion Low levels of positive mood were consistently associated with depressive symptoms scores 10 and 20 years later, suggesting clinical interventions aimed at improving positive affect may be particularly useful across the midlife.